Metal extraction from commercial black mass of spent lithium-ion batteries using food-waste-derived lixiviants through a biological process - Roy, Joseph Jegan (2025)
Lithium-ion batteries (LIBs) power most electronic devices, electric vehicles (EVs), and energy storage devices, and LIB waste is the most critical global problem in electronic waste management. However, recovering and reusing metals from discarded LIBs can reduce environmental risks and provide valuable sources of metal for new batteries. Food waste is a global issue. Most food leftovers are discarded in landfills or incinerated, with a recycling rate of approximately 10-20%. Utilizing food waste to treat LIB waste is an innovative approach that can effectively reduce waste and promote a circular economy, leading to sustainable expansion. In this innovative and environmentally friendly study, we utilize a biocatalytic procedure to transform food waste into lixiviants and extract valuable metals such as Ni, Mn, Co, and Li from spent LIBs. This study also demonstrates that gluconic acid is the primary acid produced through the enzymatic conversion of food waste into lixiviants, a sustainable process that selectively forms metal chelates with valuable LIB metals. The food-waste-derived lixiviants could extract valuable metals from LCO- and NMC-based industrial black masses at a solid content of 50 g/L with a leaching efficiency of 80-99% confirmed by inductively coupled plasma optical emission spectrometry (ICP-OES). The X-ray diffraction, scanning electron microscopy, and ICP-OES studies of LIB black masses and their leaching residues have verified that nearly all metals have been extracted from the LIB black mass. This environmentally conscious approach can efficiently extract metals from exhausted EV batteries in the interest of sustainability.